2021
DOI: 10.3389/fpubh.2021.612994
|View full text |Cite
|
Sign up to set email alerts
|

Requestioning the Indonesia Government's Public Policy Response to the COVID-19 Pandemic: Black Box Analysis for the Period of January–July 2020

Abstract: Objectives: Indonesia responded the COVID-19 pandemic slowly these last months. The recent reports shown that the rate performance of Indonesian government in handling COVID-19 posits at the 4th worst all over the world. Meanwhile, through responsive, strict, and strategic policy, some Asia countries pushed the elimination case by doing lockdown. This paper questioned how government respond this pandemic, tried to track down the unresponsive and slow decisions, and analyze them comprehensively trough policy sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…At the world level, performing the Indonesian government's policies is the 4th worst in solving the Covid-19 problem. Unfortunately, the government's ambiguous steps to comprehensively track Covid-19 do not represent a transparent framework (Ayuningtyas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…At the world level, performing the Indonesian government's policies is the 4th worst in solving the Covid-19 problem. Unfortunately, the government's ambiguous steps to comprehensively track Covid-19 do not represent a transparent framework (Ayuningtyas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The effective implementation of the epidemic emergency plan is guaranteed based on the support of a large number of emergency medical supplies (e.g., masks, testing kits and reagents, gloves, alcohol solutions, hazard material suits, etc. ), while the responses of most governments are weak in ensuring availability of much needed logistics, even if all sectors of society actively participate in the fund raising to buy supplies, the continued shortages of facilities, tools, and infrastructure for dealing with public health emergencies are difficult to be alleviated in the near future, which is detrimental to preventing the spread of an epidemic [ 49 ]. Yoo et al [ 47 ] found that a good economic support for testing and treatment is conducive to improving the compliance of citizens to epidemic emergency plans.…”
Section: Establishment Of Evaluation Criteria For Emergency Alternativesmentioning
confidence: 99%
“…For instance, pandemic demand a strong state response but the civil society's important role in holding officials accountable has been minimized (Keevill, 2020). Similarly, another example shows Indonesia's government non-disclosure of covid-19 data that infringe data transparency (Ayuningtyas et al, 2021). Although there is progress with the enforcement of public control through mass and social media, abuse of authority and power, collusion, corruption, and nepotism remain in the society (Martini, 2012).…”
Section: Introductionmentioning
confidence: 99%